2020
DOI: 10.1080/19420676.2020.1755347
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Franchising in the Bottom of the Pyramid Market: Rwanda

Abstract: This study examines how a mission-driven shared identification can help mitigate the failure of a micro-franchise in Rwanda, a bottom of the pyramid market. A single case study was adopted following Gioia's established analytical process. Interviews, semistructured interviews and observations were conducted between the period of 2018 and 2019. It was found that, a mission-driven shared identification can be achieved if a micro-franchisor promotes a culture of sharing and perceived organisational support among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Second, our research also enriches the literature on franchising in developing countries (Alon and Welsh, 2002;Kaufmann and Leibenstein, 1988;Lanfranchi et al, 2021;Welsh et al, 2006) that has mostly focused on Brazil (e.g., Bitti et al, 2019) or China (e.g., Jeon et al, 2016). Papers on franchising in Africa (e.g., Naatu et al, 2020;Perrigot, 2017Perrigot, , 2018 remain scarce despite franchising's potential for development. Third, this paper builds on the research dealing with CSR and CSD in franchise chains (Meiseberg and Ehrmann, 2012;Perrigot et al, 2015;Le Bot et al, 2022) by focusing on several dimensions of the SDGs, including, for instance, the social aspects (e.g., gender equality).…”
Section: Social Goalsmentioning
confidence: 51%
See 3 more Smart Citations
“…Second, our research also enriches the literature on franchising in developing countries (Alon and Welsh, 2002;Kaufmann and Leibenstein, 1988;Lanfranchi et al, 2021;Welsh et al, 2006) that has mostly focused on Brazil (e.g., Bitti et al, 2019) or China (e.g., Jeon et al, 2016). Papers on franchising in Africa (e.g., Naatu et al, 2020;Perrigot, 2017Perrigot, , 2018 remain scarce despite franchising's potential for development. Third, this paper builds on the research dealing with CSR and CSD in franchise chains (Meiseberg and Ehrmann, 2012;Perrigot et al, 2015;Le Bot et al, 2022) by focusing on several dimensions of the SDGs, including, for instance, the social aspects (e.g., gender equality).…”
Section: Social Goalsmentioning
confidence: 51%
“…She concluded that social franchising seems to work no differently from franchising in more traditional sectors, at least in terms of know-how management, assistance, brand name, and franchisor/franchisee and franchisee/franchisee relationships. Naatu et al (2022) showed, through a case study conducted on an anonymous micro-franchising chain in the healthcare sector in Rwanda, the importance of relying on a public-private partnership or having a governmental endorsement to succeed. Other papers included in this limited literature on franchising in African countries have dealt with dairy products, and more specifically the case of Fan Milk, which sells ice cream and yogurt in western African countries through micro-franchised street vendors in addition to supermarkets (Christensen et al, 2010;Gbetchi and Perrigot, 2020), as well as drinking water with the case of the Jibu franchise system in eastern African countries (Perrigot, 2022).…”
Section: Literature Review 21 Development Of African Economies and Fr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the weak legal systems in BOP locations encourage crime (De Beule et al, 2020; Naatu et al, 2020). Especially in Bijnor, most BOP consumers did not have bank accounts or credit cards, so they kept cash in their homes and made cash transactions with the neighbourhood retailers (Navarro, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%